2016
DOI: 10.1111/pedi.12352
|View full text |Cite
|
Sign up to set email alerts
|

Lower dose basal insulin infusion has positive effect on glycaemic control for children with type I diabetes on continuous subcutaneous insulin infusion therapy

Abstract: Low dose basal insulin infusion as a percentage of total insulin dose has a positive effect on metabolic outcome as expressed in HbA1c-levels. A change of 10% in %BD/T results in a decrease or increase of HbA1c of 0.22%. This supports the tendency to aim at the lowest basal insulin requirements in pump setting strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…Most diabetes guidelines recommend that the BI rate should be programmed in hourly intervals, according to the patient's circadian variation of insulin requirement [ 16 ] and based on their individual fasting tests over a period of 6–10 h [ 14 ]. They also suggest that a %BI range of between 30% and 50% should be used [ 1 5 , 15 , 17 ]. We found that while this recommendation on %BI was followed in more than two-third of patients with T1DM, there was a substantial proportion of individuals using a %BI outside the recommended range.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most diabetes guidelines recommend that the BI rate should be programmed in hourly intervals, according to the patient's circadian variation of insulin requirement [ 16 ] and based on their individual fasting tests over a period of 6–10 h [ 14 ]. They also suggest that a %BI range of between 30% and 50% should be used [ 1 5 , 15 , 17 ]. We found that while this recommendation on %BI was followed in more than two-third of patients with T1DM, there was a substantial proportion of individuals using a %BI outside the recommended range.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous subcutaneous insulin infusion (CSII) therapy by insulin pumps has become a widely used treatment in patients with type 1 diabetes mellitus (TIDM). CSII is currently the most physiological method of insulin delivery available [ 1 ]. This mode of insulin therapy includes two components: basal insulin (BI) infusion that mimics physiological hormone secretion during the night and between meals, and boluses of insulin substituting acute postprandial insulin secretion [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shulten et al demonstrate that low‐dose basal insulin infusion as a percentage of total insulin dose has a positive effect on metabolic outcome as expressed in HbA1c levels. They confirm that a change of 10% in basal insulin dose results in a decrease or increase of HbA1c by 0.22% . This result is consistent with the research of Strich et al, who demonstrate a significant correlation between injection of less total daily basal insulin and lower HbA1c level.…”
Section: Discussionmentioning
confidence: 99%